Pre-infusion checklist for rituximab in pemphigus vulgaris patients: clinical audit - Sagheer, Farah; Kayani, Maham; Khalil, Elma (Journal of the Pakistan Medical Association, 2023)
Objective: To evaluate whether or not the pre-infusion checklist for rituximab was followed in patients of pemphigus vulgaris. Method: The audit, intervention and re-audit was conducted at the Dermatology Department, Medical Teaching Institution-Lady Reading Hospital, Peshawar, Pakistan, and comprised in-patients of pemphigus vulgaris, confirmed by skin biopsy and immunofluorescence, who received rituximab between January 1 to March 31, 2022. The randomly picked cases were reviewed to check if the standard guidelines for rituximab prior to infusion had been followed. After completion of the first audit cycle, the medical team was give awareness about the latest pre-infusion rituximab guidelines, and they were also provided with a checklist and consent form to implement the change. Re-audit was performed from May to July, 2022, using the same method to see if improvements had been made. Data was analysed using SPSS 23. Results: Of the 20 cases evaluated against 16 parameters, the first audit showed 7(43.5%) parameters to have been met across all cases. Re-audit comprised another set of 20 cases, and showed that 15(93.75%) parameters had been applied accorss the board Pneumococcal and influenza vaccine was the only element 1(6.25%) not touching universal application. Conclusion: Re-audit showed major improvement in compliance with the standard guidelines. Key Words: Pemphigus vulgaris, Rituximab, Clinical audit, Pre-infusion guidelines.